LSTA-Swin: a long- and short-term aggregated spatio-temporal neural network for enhanced ENSO forecasting - Wei Fang; Xiao-Zhi Zhang; Yijing Li; Zhang-Jie Fu; Hai-Yan Fu (Climate Dynamics, 2026)

Assessing NEX-GDDP-CMIP6 for extreme-temperature simulation in Northwest China and projecting changes under SSP-based scenarios - Qian Li; Tongfei Zhang; Shuang Wang; Xiaohua Fu; Long Cheng; Pan Wang; Juan Feng (Climate Dynamics, 2026)

On the perturbation potential energy in the synergistic effect of ENSO and South China Sea summer monsoon on the Indian Ocean dipole development - Yazhou Zhang; Yulian Fu; Bin Zuo; Jianping Li; Yina Diao; Ting Liu; Xin Qi; Haili Wang (Climate Dynamics, 2025)

External and internal controls on decadal precipitation variability over North America - Xiaolu Fan; Jianping Huang; Yongkun Xie; Wenmin Wei; Yu Ren; Yihui Xu; Ming Peng; Li Fu (Climate Dynamics, 2025)

Intercomparison of two model climates simulated by a unified weather-climate model system (GRIST), part II: Madden–Julian oscillation - Zhen Fu; Yi Zhang; Xiaohan Li; Congwen Zhu; Hongbo Liu; Xinyao Rong; Chengming Li (Climate Dynamics, 2025)

Perspective of explosive cyclones with three shapes of upper-level potential vorticity over the northern Atlantic Ocean - J. Ni; G. Fu; L. J. Chen; P. Y. Li (Climate Dynamics, 2025)

Responses of the Arctic sea ice drift to general warming and intraseasonal oscillation in the local atmosphere - Ming Li; Xi Liang; Na Liu; Fu Zhao; Zhongxiang Tian (Climate Dynamics, 2024)

Intercomparison of two model climates simulated by a unified weather-climate model system (GRIST), part I: mean state - Zhen Fu; Yi Zhang; Xiaohan Li; Xinyao Rong (Climate Dynamics, 2024)

Assessment and prediction of regional climate based on a multimodel ensemble machine learning method - Yinghao Fu; Haoran Zhuang; Xiaojing Shen; Wangcheng Li (Climate Dynamics, 2023)

The dynamics of the equatorial Atlantic upwelling seasonal cycle under global warming and its potential impact on Pacific ENSO - Li-Chiao Wang; Thi Lan Dao; Yong-Fu Lin; Jia-Yuh Yu (Climate Dynamics, 2023)

Impacts of the long-term atmospheric trend on the seasonality of Antarctic sea ice - Fu Zhao; Xi Liang; Zhongxiang Tian; Chengyan Liu; Xichen Li; Yun Yang; Ming Li; Na Liu (Climate Dynamics, 2023)

The role of sea surface temperature variability in changes to global surface air temperature related to two periods of warming slowdown since 1940 - Yidan Xu; Jianping Li; Haohuan Fu (Climate Dynamics, 2022)

Nonlinear optimal moisture perturbations as excitation of primary MJO events in a hybrid coupled climate model - Yuntao Wei; Hong-Li Ren; Mu Mu; Joshua-Xiouhua Fu (Climate Dynamics, 2020)
Although the moisture feedback has been well known to be essential in the Madden–Julian Oscillation (MJO) dynamics, whether its pre-moistening effect plays a key role in exciting the onset of primary MJO events, as has been confirmed in the successive initiation, remains elusive. In this study, using a hybrid coupled climate model that has a good fidelity in simulating the intraseasonal variability, we develop a new framework of methodology to investigate the nonlinear excitation of primary MJO event, of which the key achievement is the successful implementation of the conditional nonlinear optimal perturbation (CNOP). In an application of this new framework, the CNOP-type moisture perturbations are calculated for the pre-chosen non-MJO reference states and generally favor a moistening in the equatorial region while drying in the poleward. Comparisons of the model simulation with observation give credibility to the existence of moisture signals several weeks before some primary MJO events. A suite of numerical experiments confirms that the CNOPs of moisture can contribute to the excitation and propagation of strong primary MJO events while random perturbations cannot. The moisture budget analysis further reveals the central importance of the horizontal moisture advection, especially the nonlinearly upscaled moisture transports associated with the high-frequency disturbances on the quasi-3–4-day and 6–8-day synoptic time scales, in supporting the nonlinear excitation of the primary MJO events. The subgrid-scale processes of evaporation, condensation and eddy transport of moisture are found to be critical for the pre-moistening effect in the boundary layer as well. This study directly supports the vital importance of the moisture perturbations, which are characterized by a particular pattern concentrated at low levels, to the nonlinear growth and propagation of the primary MJO events.

Near-equatorial tropical cyclone formation in western North Pacific: peak season and controlling parameter - Yan Li; Tim Li; Caifang Fu; Pang-Chi Hsu (Climate Dynamics, 2019)

Precipitation characteristics over the steep slope of the Himalayas in rainy season observed by TRMM PR and VIRS - Yunfei Fu; Xiao Pan; Tao Xian; Guosheng Liu; Lei Zhong; Qi Liu; Rui Li; Yu Wang; Ming Ma (Climate Dynamics, 2018)

Three different downstream fates of the boreal-summer MJOs on their passages over the Maritime Continent - Joshua-Xiouhua Fu; Wanqiu Wang; Hong-Li Ren; Xiaolong Jia; Toshiaki Shinoda (Climate Dynamics, 2018)

Sensitivity of a regional climate model to land surface parameterization schemes for East Asian summer monsoon simulation - Wenkai Li; Weidong Guo; Yongkang Xue; Congbin Fu; Bo Qiu (Climate Dynamics, 2016)

Effects of air–sea coupling on the boreal summer intraseasonal oscillations over the tropical Indian Ocean - Ailan Lin; Tim Li; Xiouhua Fu; Jing-Jia Luo; Yukio Masumoto (Climate Dynamics, 2011)

Changes in cloudiness over the Amazon rainforests during the last two decades: diagnostic and potential causes - Paola A. Arias; Rong Fu; Carlos D. Hoyos; Wenhong Li; Liming Zhou (Climate Dynamics, 2011)

Diurnal phase of late-night against late-afternoon of stratiform and convective precipitation in summer southern contiguous China - Rucong Yu; Weihua Yuan; Jian Li; Yunfei Fu (Climate Dynamics, 2010)